Job Performance Evaluation of Medical Social Workers during Covid-19 Crisis: Tasks, Attitudes, and Difficulties - Walaa Elsayed (Ital Publication, 2023)
Objectives: The objective of this study is to evaluate the job performance efficiency of social workers in medical institutions during the COVID-19 pandemic crisis, based on three factors